1971
DOI: 10.1113/jphysiol.1971.sp009441
|View full text |Cite
|
Sign up to set email alerts
|

Heat production in the gastro‐intestinal tract of the dog

Abstract: SUMMARY1. Mean temperature from the lumen of the dog duodenum was 0.6 C hotter than aorta. Ileum, stomach and large intestine were slightly cooler but still about 0.50 C hotter than aorta.2. Portal vein averaged 0.35°C hotter than the aorta. 3. From portal blood flow data and aortic-portal temperature differentials heat production was calculated for the 10 kg dog as 3-4 kcal/hr.Evidence is adduced to show in these experiments that the gastrointestinal tract produced 60 % more heat than the liver. Total splanch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…However, we should note that duodenal and jejunal blood flows are comparable (Delaney & Custer, 1965). Our own work also indicates that resting heat production is similar in the two regions (Durotoye & Grayson, 1971). However, these observations may not be relevant.…”
Section: Discussionmentioning
confidence: 60%
“…However, we should note that duodenal and jejunal blood flows are comparable (Delaney & Custer, 1965). Our own work also indicates that resting heat production is similar in the two regions (Durotoye & Grayson, 1971). However, these observations may not be relevant.…”
Section: Discussionmentioning
confidence: 60%
“…It has become apparent in r e c e n t y e a r s that the metabolic activity of the bowel in t e r m s other than active transport or smooth muscle activity is g r e a t e r than had been previously thought likely (Durotoye and Grayson, 1971;Hartialla, 1968). The p r e s e n t authors have more recently shown (unpublished) a close link with the l i v e r in r e s p e c t of glucose metabolism, with insulin and glucagon playing c r u c i a l r o l e s in the control of bowel glucose metabolism, oxygen consumption and heat p r oduction.…”
Section: Discussionmentioning
confidence: 95%
“…It is now clear, however, that in a thermo-neutral environment it accounts for at least 25% of the total heat production of the body (Grayson et al, 1971). Temperatures as high as 0.7°C above aortic may frequently be recorded from the lumen of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent work it was shown that oxidative processes alone could not account for this level of heat production. There was a net uptake of glucose far in excess of that which could be accounted for on the basis of oxidative metabolism alone (Durotoye & Grayson, 1971).…”
Section: Introductionmentioning
confidence: 99%